(untitled) (Ustozlar uchun, 2026)
Jane Austen’s Pride and Prejudice (1813) remains one of the most widely read and critically celebrated novels in the English literary canon. Through the witty and perceptive narrative of Elizabeth Bennet, Austen dissects the social structures of Regency-era England, challenging conventions of marriage, class, and gender with remarkable subtlety. This article examines the central themes of the novel — including pride, social prejudice, the institution of marriage, and female independence — while exploring Austen’s narrative techniques such as free indirect discourse, irony, and satirical characterization. Drawing on primary textual evidence and secondary scholarly sources, this analysis argues that Pride and Prejudice transcends its historical moment to offer enduring insight into human nature, self-knowledge, and the tension between individual desire and social obligation.